ON THE HORNS OF A DILEMMA: INTELLECTUALS BETWEEN THE REGIME AND THE PEOPLE AS REFLECTED IN IRAQI COMMUNIST LITERATURE - Peled-Shapira, Hilla (The Levantine Review, 2012)
This paper deals with the way in which Communist writers in mid-twentieth-century Iraq used literature in order to, on the one hand express their tense relationship with the regime during times of severe political repression, and on the other hand sharply criticize the Iraqi people themselves for not taking responsibility for or caring about their fate—or, for that matter, for failing to internalize the social class discourse to which the Communists aspired. The paper’s objective is to examine the connection between the writers’ ideology and the rhetorical and conceptual elements with which they expressed their dissatisfaction with the regime, the way Iraqi society was run, and the desires of both—intellectuals and society at large—to undergo change. In addition, this study will survey the esthetic and stylistic devices, which the writers under consideration chose, and consider both the meanings and motives behind their choices. These aspects will be examined in the framework of a proposed model of “circles of criticism.”